(untitled) (Academia Journal of Medicine, 2023)
Background: To present thromboembolic complications after recovery from covid-19 and determine its Association with CT severity score. Subjects and Methods: An observational study was conducted retrospectively over a period of 1 month during which all cases who presented with thromboembolic complications after being discharged from covid-19 were enrolled. The data pertaining to the socio-demography, haematological parameters and inflammatory markers such as LDH, IL-6, ferritin, CRP and D-Dimer were recorded at the time of admission with COVID-19. Initial chest HRCT scans were done at presentation. For determining the area of embolism, CT angiography was done in the region of head and neck, coronary and lower limb as per the presenting symptoms. The patients were thrombolysed/ revascularized and followed up until recovery/death. Results : HRCT scoring was normal in 59.18% cases, mild in 8.16% and severe in 32.65% cases. Thromboembolic complications were seen in all patients, common being peripheral vascular disease (53.06%) followed by coronary artery disease (38.78%) and lastly cerebrovascular accidents (8.16%). Mean value of post covid days of study subjects was 12.33 ± 5.34 with median (25th-75th percentile) of 11(8-16). There was only a single mortality in the present study. HRCT score showed a significant association with the presence of hypertension (p=0.011,) and leukocytosis (p=0.004). However there was no significant association of HRCT with the region of thromboembolism. Conclusions: Thromboembolic complications are common in the initial month of post covid phase. Comorbidities like hypertension needs to be controlled as it shows a significant association with HRCT severity. Inflammatory levels of IL-6 and CRP may be implicated in the occurrence of thromboembolism. An early identification, treatment and thromboprophylaxis is required in such cases for a better outcome.